The effect of reality therapy group counseling on pregnant women’s sexual function: An interventional study - Fatemeh Bahadori; Mahtab Attarha; Fatemeh Mehrabi Rezveh (حیات)
Background & Aim: Pregnant women experience physiological changes and may fear harming themselves or their fetus, leading some to avoid sexual intercourse during pregnancy. This avoidance can lead to sexual health issues. This study aimed to investigate the effect of reality therapy group counseling on the sexual function of pregnant women. Methods & Materials: This interventional study was conducted with 80 pregnant women referred to health centers in Arak in 2019. Participants were selected through convenience sampling and randomly assigned to either the intervention group or the control group (40 participants in each group). The intervention group received eight sessions of reality therapy group counseling over four consecutive weeks, while the control group received routine prenatal care. Participants completed the standard Female Sexual Function Index (FSFI) questionnaire before the intervention and four weeks after the sessions. Data was analyzed using SPSS software version 16, employing paired t-tests, independent t-tests, and the Mann-Whitney U test. Results: There was no statistically significant difference in the mean score of sexual function between the two groups before the intervention (P=0.573). However, four weeks after the intervention, the mean score of sexual function in the intervention group (27.22±2.91) significantly increased compared to the control group (20.32±0.31) (P<0.001). Conclusion: Implementing group sexual counseling based on the reality therapy approach can improve sexual performance among pregnant women. Thus, it is recommended that midwives employ this approach to improve the sexual function of pregnant women.